The incidence and outcomes of uterine rupture in a tertiary hospital. (18th April 2012) - Chandranath, DI; Anbazhagan, A; Zawislak, A
Abstract : Background: Previous caesarean section, fetal macrosomia, induction and augmentation of previous sections are factors that significantly increase the rate of scar dehiscence and uterine rupture. Method: A total of 5549 deliveries were recorded at Royal Maternity Hospital, Belfast during a period of 1 year, of which 9 cases were identified as ruptures or dehiscence. These cases were reviewed for complications, mode of induction, presentation and identification of risk factors. Results: We found 6 ruptures and three scar dehiscence during our period of observation (0.1%). There were no maternal or neonatal deaths. One patient (11%) was admitted to the ICU and 1 baby (11%) to NNU. Interestingly 55% of our patients presented with abdominal pain and vaginal bleeding, whereas 22% accounted for abnormal CTG. 50% ruptured during labour and the other 50% were emergency admissions with symptoms of collapse (33%). >50% of the IOL ruptured. All patients had one or two previous sections. Caesarean Hysterectomies (11%), maternal blood transfusion (55%) and babies having apgars <7 at 5 mins(12.5%) were some of the complications noted. Fetal macrosomia, morbid obesity and PGE2 induction were independently associated with uterine rupture and scar dehiscence. Conclusion: Abdominal pain and vaginal bleeding are equally if not more significant in raising the suspicion of rupture or dehiscence than abnormal CTG. Carefully selecting patients for VBAC with an early senior input and continuous intra-partum monitoring will reduce the risk of ruptures. Previous scar predisposes to uterine rupture therefore all effort should be made to avoid the first caesarean section.